MONITORING OF DRINKING WATER RESERVOIRS OF KOPARGAON CITY WITH SPECIAL REFERENCE TO ALGAL FLORA AT YESGAON, DIST. AHMEDHNAGAR MAHARASHTRA (M.S.), INDIA - Sanap, R. R.; Shevare, B. P.; Barwant, M. M. (International Journal of Research -GRANTHAALAYAH, 2020)
Algal collection from 5 drinking water storage reservoirs of Kopargaon city was carried out for one year. A total 39 genera and 62 species belonging to four classes were encountered during investigation period. Present studies revealed that, algal population was not found homogenous throughout the year, but it showed seasonal variation. During monsoon the algal population recorded was less, which increases in winter and found more in summer season. Chlorophyceae was found to be the dominant group throughout the investigation period in all storage tanks consisting of large number of genera and species. Many planktonic, some benthic and epiphytic algae were encountered during investigation period at all five water storage reservoirs. The commonly occurred genera were Ankistrodesmus, Closterium, Cosmarium, Spirogyra, Ulothrix from class Chlorophyceae, while from Cyanophyceae, Merismopedia, Microcystis, Oscillatoria, and Lyngbya are dominating forms. Desmids wear found in dominant condition in all storage tanks indicating unpolluted condition of water. Maximum population of Cosmarium was recorded during summer season, while Closterium species were recorded throughout the year. Other genera recorded were Staurastrum, Xanthidium, Euastrum, Micrasterias, Arthrodesmus, Desmidium, etc. Diatoms were recorded more in number during winter, while Euglenophycean members were sparsely reported only in summer. During present studies tremendous variations in Desmid diversity was noticed during summer and winter as compared to monsoon season.